A music therapy group for gay men: thoughts and considerations. (1st June 2016) - Aronoff, Uri
Abstract : Background : Sexual identity formation process can often be accompanied by a sense of loneliness, difficulties in relationships, shame and lack of self-acceptance. Previous research I conducted showed that music can have different roles in the process of coming out and sexual identity formation. Objective : To present the clinical work, I did with a music therapy group for gay men using existing songs. Methods : A group of six gay men was formed through The LGBT organization in Tel Aviv. The clinical work was based on the use of Amir's (2012) musical presentation model (MPM) in which participants introduced themselves to the group through songs of their choice. Results : The musical group work improved the ability of the participants to experience intimacy and empathy towards others; it increased their feelings of belonging to the gay community and developed acceptance of their own sexual identity. Discussion : The roles of MPM, particularly the fact that presenting songs to others, helped the participants to express their inner world and to concurrently receive support from peers.